2017
DOI: 10.1021/acschemneuro.7b00197
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Transcriptomic Data with Mechanistic Systems Pharmacology Models for Virtual Drug Combination Trials

Abstract: Monotherapy clinical trials with mutation-targeted kinase inhibitors, despite some success in other cancers, have yet to impact glioblastoma (GBM). Besides insufficient blood-brain barrier penetration, combinations are key to overcoming obstacles such as intratumoral heterogeneity, adaptive resistance, and the epistatic nature of tumor genomics that cause mutation-targeted therapies to fail. With now hundreds of potential drugs, exploring the combination space clinically and preclinically is daunting. We are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Historically dysfunctions of the BBB are associated with the onset and progression of different neurological disorders including Alzheimer's disease [26], epilepsy [27], stroke [28,29], multiple sclerosis [30], traumatic brain injury [31], amyotrophic lateral sclerosis [32] as well as schizophrenia [33]. Observed changes include alterations in BBB permeability [34,35], caused by disruption and/ or structural alteration of TJ proteins [36]. This process can be associated with the degradation of the basement membrane [37] and altered expression of efflux pumps leading to the extravasation of plasma proteins [38,39].…”
Section: Bbb Dysfunction In Neurological Disordersmentioning
confidence: 99%
“…Historically dysfunctions of the BBB are associated with the onset and progression of different neurological disorders including Alzheimer's disease [26], epilepsy [27], stroke [28,29], multiple sclerosis [30], traumatic brain injury [31], amyotrophic lateral sclerosis [32] as well as schizophrenia [33]. Observed changes include alterations in BBB permeability [34,35], caused by disruption and/ or structural alteration of TJ proteins [36]. This process can be associated with the degradation of the basement membrane [37] and altered expression of efflux pumps leading to the extravasation of plasma proteins [38,39].…”
Section: Bbb Dysfunction In Neurological Disordersmentioning
confidence: 99%
“…For instance, specific mutations in a patient can render a protein dysfunctional, and this information can be encoded in the model by removing certain nodes (proteins) or edges (interactions). Proteomic data, or transcriptomic data as a proxy, can inform on protein levels and can be used to reparametrize and personalize cell‐line‐derived models (Fey et al , ; Barrette et al , ).…”
Section: Schematic Of the Cycle To Generate Patient‐specific Dynamic mentioning
confidence: 99%
“…Parameterization of kinetic models can be challenging. Recently, it has been shown that transcriptomic profiling data derived from glioblastoma patient-derived tumor samples can be used to inform kinetic systems pharmacology models to conduct virtual drug combination trials (111). Another example described the prediction of combination therapies for B-cell lymphoma using a kinetic model of the B-cell receptor signaling network (112).…”
Section: Analysis Of Molecular Drug-disease Network Interactionsmentioning
confidence: 99%